Health-Related Quality of Life in Predominantly Young Parental Living Liver Donors: A Cross-Sectional Study in China - Shi, Yue-Xian; Zhang, Hai-Ming; Chen, Jing; Huang, Ya-Qi; Yu, Ming-Ming; Jin, Yin-Hui; Wang, Wen-Ru; Gao, Wei (Frontiers in Medicine, 2021)
Objective: The health-related quality of life (HRQoL) of donors deserves attention and must be considered for a long time. Many of the published studies had small sample sizes, and research from mainland China, in particular, is scant. Thus, this study aimed to investigate the HRQoL of living liver donors and identify the influencing factors of the HRQoL in mainland China. Methods: This is a cross-sectional study. The data were collected from the liver transplantation center, the Tianjin First Center Hospital, China. Living liver donors older than 18 years and at a minimum of 1-month, post-donation was included. The HRQoL was evaluated using the Medical Outcome Study Short form 36 (SF-36). Sociodemographic and clinical-related variables, HRQoL status, and its potential impact factors were analyzed. Results: A total of 382 living liver donors completed the survey. The median number of months post-donation was 25, and parental donors (99.2%) were the most frequent relationship. The majority of the participants (372, 97.4%) donated their left lateral lobes. Thirty-two (8.4%) donors suffered complications, and of them, 7 suffered from biliary leakage (1.8%), which was the most common one in this study. The physical functioning (PF), role–physical (RP), bodily pain (BP), general health (GH), social functioning (SF), role–emotional (RE), and mental health (MH) scores among the living liver donors were significantly better than those of the Chinese norms. Short-time post-donation [odds ratio (OR): 0.008; p < 0.001] and male recipients (OR:0.195; p = 0.024) were associated with the likelihood of a poor physical related quality of life. Conclusions: Despite, in general, good HRQoL outcomes, we also believed that liver donation has an obvious influence on the physical functions of liver donors. More attention and long-term follow-ups are necessary for donors at higher risk based on identified influencing factors and correlates.